Fitoremediasi Air Tercemar Polutan Amoniak Dengan Memanfaatkan Eceng Gondok (Eichornia Crassipes) - Fariez Fariez; Chairul Chairul; Said Said; ZA ZA (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Contaminated wastewater pollutants ammonia can be done by phytoremediation using water hyacinth plants (Eichornia crassipes). To determine the absorption ability of water hyacinth to the polluted water of ammonia, a number of water hyacinth plants were placed in a test reactor, each filled with artificial water contaminated with ammonia 4x as much as 16 liters for 24 hours. Taken every 24 hours water sample is taken from each test reactor for analysis using a spectrophotometer at 640nm wavelength λ. The results showed that the longer the higher the percentage of absorption of dissolved ammonia absorption by water hyacinth plants in each test reactor nutrition factors in addition to the water hyacinthplants.  Keywords: Water Hyacinth (Eichornia crassipes), pollutants ammonia, phytoremediation